Sprouty2 protein in prediction of post-treatment ascites in epithelial ovarian cancer treated with adjuvant carbotaxol chemotherapy - Masoumi-Moghaddam, Samar (Am J Cancer Res, 2015)
Ascites development and resistance to chemotherapy with carbotaxol are common clinical problems in epithelial ovarian cancer, partly due to the activation of MAPK/ERK signaling. Sprouty proteins are negative modulators of MAPK/ERK pathway, but their role in predicting resistance to carbotaxol chemotherapy and ascites development is unknown. In this study, we evaluated the expression of Sprouty protein isoforms by immunohistochemistry. The associations between the Sprouty expression and the clinicopathological features, including chemoresistance and the presence of ascites, were then explored. We found that the decreased expression of Spry2 was correlated with the post-treatment development of ascites and represented an independent predictor of this condition in carbotaxol-treated patients. However, no association was observed between the Sprouty expression and chemoresistance. In conclusion, our results suggest that Spry2 may be useful for patient follow-up and monitoring as it predicts the development of ascites in epithelial ovarian cancer cases treated with carbotaxol.